Novosorb® BTM- history, production and application in challenging wounds - Rajaram, Rohan; Zhang, Min; Premaratne, Gehan; Ng, Sally (Frontiers in Bioengineering and Biotechnology, 2024)
Novosorb® Biodegradable Temporizing Matrix (BTM) is an entirely synthetic dermal matrix that is gaining popularity in the management of challenging wounds. Not only does it provide a framework in which to grow an organised neodermis, it is also especially resistant to infection. Today, the matrix is available as a 2mm thick open cell polyurethane foam with a non-degrading sealing membrane. Its current form is the result of numerous in vitro and in vivo experiments that examined its shape, biodegradation, inflammatory response, and cytotoxicity. Clinical data on the use of BTM in a variety of cases is novel and presents early insights into its ability to foster wound healing where otherwise improbable. This review presents the history and development of Novosorb® BTM as well as all the currently available clinical data on its efficacy in difficult wounds such as: major burns, necrotising soft tissue infection, chronic wounds and in non graftable wound beds.